1996
DOI: 10.1063/1.472931
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent charge transfer in a beam of CO++ colliding with Ar, N2, H2, D2 and CO

Abstract: Luminescent charge transfer of CO++(3Π,1Σ+) ions in a beam with several atomic and molecular target species in a scattering cell was observed at 60–2000 eVlab projectile energies. Emission from CO+(B 2Σ+→X 2Σ+) was spectrally analyzed with a resolution of up to 1 Å full width at half maximum. In the case of CO+++CO collisions, CO+(B) emission due to electron capture by the projectile and to target ionization were distinguished using isotopic substitution. CO+(A 2Π→X 2Σ+) emission from the ionized target was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Dynamics at the crossings with the A ϩ ϩB ϩ surfaces is well understood by the simple ''reaction window'' concept based on the Landau-Zener model, [43][44][45] and has been the subject of detailed discussions in recent papers. 7,8 The key point of the reaction window approach is that the charge transfer is effective whenever the crossing occurs at internuclear distances between 2 and 6 Å.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dynamics at the crossings with the A ϩ ϩB ϩ surfaces is well understood by the simple ''reaction window'' concept based on the Landau-Zener model, [43][44][45] and has been the subject of detailed discussions in recent papers. 7,8 The key point of the reaction window approach is that the charge transfer is effective whenever the crossing occurs at internuclear distances between 2 and 6 Å.…”
Section: Resultsmentioning
confidence: 99%
“…Absolute integral cross sections are obtained by ϭaI p /I s , where a is a constant, I p is the intensity of the product ions, and I s is the intensity of the reactant ions. The constant a is determined by normalizing our data on those obtained by Ehbrecht et al, 8 who measured the cross section for the formation of Ar ϩ -reaction ͑1͒ -at 18 eV ͑C. M.͒ to be 1.90 Å 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] In these states the bonding interaction is sufficient to overcome the Coulombic repulsion between the positive charges, and there has been a recent upsurge of interest in studying the properties and reactivity of such longlived multiply charged ions. 23,[26][27][28][29] For Cl 2 , Heron and Diebler 30 observed long-lived Cl 2 2ϩ ions in electron-impact mass spectra in 1960 and determined their appearance energy as 32.6 eV. This observation was rationalized when ab initio calculations showed that the ground state of Cl 2 2ϩ possessed a significant metastable well.…”
Section: Introductionmentioning
confidence: 97%
“…Single-electron transfer (SET) reactivity, which is close to ubiquitous in collisions of small dications with neutrals, has been extensively studied and is now reasonably well understood. [7][8][9][10][11][12][13][14][15][16][17][18] Specifically, the "reaction-window" concept, arising from an application of Landau-Zener theory to dication-neutral collisions, readily explains the SET reactivity in these encounters at low collision energies. [9][10][11]13,14,[18][19][20][21][22] Scattering experiments, employing crossed-beam mass spectrometers, guided ion beams and coincidence techniques, have also been used to elucidate the detailed mechanisms of dicationic SET reactivity, usually revealing a direct pathway.…”
Section: Introductionmentioning
confidence: 99%